Inicjatywa lokalna jako jedna z prawnych form partycypacji społecznej na przykładzie Miasta Lublin - Księski, Krzysztof (Studia Prawa Publicznego, 2026)
This article discusses the institution of local initiatives as a specific, legally regulated form of social participation in Poland, with particular emphasis on their operation in the city of Lublin. The aim of the study is to analyse the normative structure of this institution, assess its importance in the public governance system, and verify its practical application at the local government level in Lublin. The author uses a dogmatic legal approach, analysing the provisions of the Act on Public Benefit Activities and Volunteering, as well as local law, case law, and legal scholarship. This is complemented by an empirical analysis based on data on local initiatives in Lublin, including the number of submitted applications, their effectiveness, and budgetary and organizational conditions. The article demonstrates that local initiatives have a hybrid legal nature, combining elements of administrative and civil law, and constitute an instrument for implementing the principle of subsidiarity and developing civil society. At the same time, it identifies numerous barriers limiting their practical application, such as legislative shortcomings, low social participation, and the limited involvement of local government units. The case study of Lublin confirms the marginal importance of this institution in practice, which leads to the conclusion that local initiatives have untapped potential as a tool for social participation.